Analisis Implementasi Pemberlakuan Undang-Undang Nomor 1 Tahun 2022 Tentang Hubungan Keuangan Antara Pemerintah Pusat Dan Pemerintah Daerah Pada Pajak Bumi Dan Bangunan Di Badan Pengelola Pendapatan Daerah Kota Cimahi - Dian Kaniawati; Eko Setyanto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Regional governments regulate and manage their own government affairs according to the principle of autonomy and co-administration that in order to create an effective and efficient allocation of national resources, it is necessary to regulate the management of financial relations between the central government and regional governments that are just, harmonious and accountable based on Pancasila and the Law of the Republic of Indonesia. The 1945 Constitution of the Republic of Indonesia. The research method used in this study is a descriptive method with a qualitative approach. Data collection techniques used include library research, field research, and interviews. Then the informants in this study were 6 people, who were determined purposively. The data analysis was carried out through triangulation. The results of the study concluded that the Potential Realization of Certain Land and Building Tax Revenues from Land and Building Tax in Cimahi City in the Next 5 Years will experience a significant increase